Atmospheric learning: Pengembangan digital mind maps berbantuan mind mapping software untuk siswa Geografi SMA - Selvi Nanda Oktavia; Ardyanto Tanjung; Listyo Yudha Irawan (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2021)
Learning media is a tool for students to make learning easier. Mind map digital is a learning media in the form of mind maps with the help applications of mindset mind manager presentation. The main objective of developing mind maps is to produce digital-based products for class X students on material atmospheric. This media can be a reference for the latest material, examples and learning resources around the atmosphere to provide students with an easy understanding of the lesson. The mind map digital developed has been tested internally by media experts and material experts. The final results are in the form of a digital mind map product design that has been revised based on suggestions and recommendations from each validator. This research and development use the modified ADDIE’s model only in the ADD section with research procedures namely goal formulation, media design, media validation. The research subjects were 28 students of class X IPS 4 in SMA 2 Batu. The research data used included the results of the media feasibility questionnaire, while the techniques data analysis used descriptive analysis to process the trial data. The results showed that digital mind maps were feasible to be used in the learning process with each gaining scores from material experts 98 percent and media experts 79 percent. Then the assessment or product response from students as research subjects get a value of 80.02 percent. Media pembelajaran merupakan alat bantu untuk peserta didik agar memberikan kemudahan dalam belajar. Mind map digital adalah media pembelajaran dalam bentuk peta pikiran dengan berbantuan aplikasi presentasi mindjet mindmanager. Tujuan utama pengembangan mind map adalah menghasilkan produk berbasis digital untuk peserta didik kelas X pada materi atmosfer. Media ini dapat menjadi rujukan materi, contoh, dan sumber belajar terbaru seputar atmosfer untuk memberikan peserta didik kemudahan dalam memahami pelajaran. Mind map digital yang dikembangkan telah di uji internal oleh ahli media dan ahli materi. Hasil akhir berupa rancangan desain produk mind map digital yang telah direvisi berdasarkan saran dan rekomendasi dari masing-masing validator. Penelitian dan pengembangan ini menggunakan model ADDIE yang dimodifikasi hanya pada bagian ADD dengan prosedur penelitian yaitu perumusan tujuan, desain media, validasi media. Subjek penelitian adalah 28 peserta didik kelas X IPS 4 SMA 2 Batu. Data penelitian yang digunakan meliputi hasil angket kelayakan media, sedangkan teknik analisis data menggunakan analisis deskriptif untuk mengolah data hasil uji coba. Hasil penelitian menunjukkan bahwa mind map digital layak digunakan dalam proses pembelajaran dengan masing-masing memperoleh nilai dari ahli materi 98 persen dan ahli media 79 persen. Kemudian penilaian atau tanggapan produk dari peserta didik selaku subjek penelitian mendapatkan nilai 80,02 persen.